2021
DOI: 10.1177/02692155211006865
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of perioperative pain science education on pain, psychological factors and physical functioning: A systematic review

Abstract: Objective: To synthesize the evidence on the effectiveness of pain science education on pain, psychological factors and physical functioning in adults who underwent surgery. Data sources: A systematic literature search of English articles using PubMed/Medline, Embase, Web of Science Core Collection, and Cochrane Library. Review methods: The search strategy was constructed as follows: (((pain) AND (education)) OR (pain education)) AND (surgery). Only controlled quantitative studies in adults reporting outcome(s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…Van der Gucht et al (2021) found that preoperative pain science education did not result in significant effects on pain, psychological factors or physical functioning compared to controls , in patients waiting to undergo total knee arthroplasty.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Van der Gucht et al (2021) found that preoperative pain science education did not result in significant effects on pain, psychological factors or physical functioning compared to controls , in patients waiting to undergo total knee arthroplasty.…”
Section: Resultsmentioning
confidence: 84%
“…Small significant effects were also found for reducing postoperative anxiety, depression, and enhancing satisfaction. Van der Gucht et al (2021) found that preoperative pain science education did not result in significant effects on pain, psychological factors or physical functioning compared to controls, in patients waiting to undergo total knee arthroplasty.…”
Section: Educational Interventionsmentioning
confidence: 84%
See 1 more Smart Citation
“…These activities can help patients relax and reduce feelings of tension and anxiety. [27][28][29][30] TACE intervention surgery is an invasive procedure, and the surgical incision can cause varying degrees of postoperative pain in patients. Additionally, the surgical process may stimulate the digestive system, thereby affecting postoperative digestive function.…”
Section: Discussionmentioning
confidence: 99%
“…Van der Gucht and colleagues recently published a systematic review examining the efficacy/effectiveness of educationally-based interventions designed to improve patients’ abilities to cope with pain. 1 I had a particular interest in this systematic review because Van der Gucht et al included our recently published trial 2 in the review and requested additional information, which we provided. The topic is an important one but with any systematic review, the information from each trial must be accurate for the reader to fully understand the meaning of a body of evidence.…”
mentioning
confidence: 99%